Site selection study of siren early warning system for community preparedness due to potential dam calamity: case study of Kg Batu Melintang, Jeli, Kelantan - Mamat, Ahmad Fadhli; Md Amin, Mohammad Faiq; Mahmood, Jaini; Abd Hamid, Mohamad Amirul Hafiz; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Muda, Rahsidi Sabri (IOP Publishing, 2025)
Effective early warning systems (EWS) for dam disasters rely heavily on the strategic placement of sirens to ensure comprehensive coverage and timely alerts. This study investigates the criteria and methodologies for optimizing siren placement, utilizing Geographic Information System (GIS) technology and multi-criteria decision analysis. By integrating data on population density, geographic features, and flood hydrodynamics, the study identifies optimal siren locations to maximize effectiveness. Population data from recent census reports, geographic data from topographic maps and satellite imagery, and disaster simulation data were analysed to determine high-risk areas and prioritize siren placement. The results demonstrate that strategic placement of sirens with standard coverage radius of up to 1 kilometre can significantly enhance early warning capabilities, even in areas prone to flooding, provided they are strategically placed in densely populated zones. The findings highlight the importance of data-driven site selection in improving disaster preparedness and risk management strategies, ultimately contributing to more effective early warning systems that safeguard lives and property in vulnerable communities.